Sick leave and disability pension before and after initiation of antirheumatic therapies in clinical practice. Issue 8 (25th April 2011) - Neovius, M; Simard, J F; Klareskog, L; Askling, J; ,
Abstract : Objective: To investigate sick leave and disability pension in rheumatoid arthritis (RA) in relation to the initiation of biological and non-biological antirheumatic therapies in clinical practice. Methods: Patients aged 19–60 years initiating non-biological mono (n=2796) or combination disease-modifying antirheumatic drug (DMARD) therapy (n=973), or biological agents (n=4787) were identified in the Swedish Rheumatology Quality Register between 1999 and 2007. Sick leave and disability pension data (1995–2010) were retrieved from national registers. Results: During the year before the start of mono DMARD, combination DMARD and biological treatment, 10%, 12% and 43% of patients received disability pension benefits, respectively. The corresponding combined annual sick leave and disability pension days were 78 (54+25), 132 (105+27) and 190 (79+111). Irrespective of treatment type, initiators were characterised by a history of increasing sick leave and disability pension. Treatment start was associated with a break in this trajectory: sick leave decreased while disability pension increased, resulting in a net stabilisation of total days. Higher levels of days on sick leave and disability pension at treatment start were observed in patients initiating biologics in 1999 (236 days/year) compared with 2007 (150 days/year; p<0.001), but the trajectory thereafter remained largely similar and contrasted markedly with the level in the general population. Conclusion: Sick leave and disability pension increased rapidly before the initiation of antirheumatic therapy, which was associated with a halt but not a reversal of this development. Work ability is a metric of importance for clinical practice, signalling large remaining needs in the RA population, and the need for intervention earlier in the disease process.